CESAR VIRATA at finance: Tax collector and reformer, 1970 to 1986 - Gerardo P. Sicat (University of the Philippines, School of Economics (UPSE), 2011)
Cesar Virata's tenure as secretary/minister of Finance is the longest held by any head of department in Philippine history. This study reviews his contributions to the evolution and reform of the Philippine tax system which were significant, sustained and consistent. His contributions helped to bring the internal and customs revenues of the country toward their present state.
Keywords: 330; Tax reform; Tax administration; Income taxation; Sales taxation; Economic development; Customs administration; Smuggling; Protectionism; Cesar Virata; Philippine economic history; Steuerreform; Finanzverwaltung; Einkommensteuer; Illegaler Handel; Wirtschaftsgeschichte; Philippinen